Highly Water-Preserving Zwitterionic Betaine-Incorporated Collagen Sponges With Anti-oxidation and Anti-inflammation for Wound Regeneration - Chen, Anqi; An, Ying; Huang, Wen; Xuan, Tengxiao; Zhang, Qianwen; Ye, Mengqi; Luo, Sha; Xuan, Xuan; He, Huacheng; Zheng, Jie; Wu, Jiang (Frontiers in Cell and Developmental Biology, 2020)
A core problem in wound healing – with both fundamental and technological significance – concerns the rational design of bioactive and moist microenvironments. Here, we design a new class of zwitterionic betaine-incorporated collagen sponges (BET@COL) with integrated anti-oxidation and anti-inflammatory properties for promoting wound healing in a full-thickness removal wound model. The presence of zwitterionic betaine in a 3D network structure of collagen enables tightly bind and lock of water molecules inside sponges via ionic solvation and confinement effect, while the integration of this zwitterionic amino acid derivative also allows to empower the sponge with anti-oxidation and anti-inflammatory functions. In vitro results demonstrated that BET@COL collagen sponges not only strongly preserved water content up to 33.78 ± 0.78% at 80th minute at 37℃ (only 0.44 ± 0.18% in collagen sponge only), but also exhibited high cell biocompatibility. Further, BET@COL collagen sponges with different betaine contents were applied to a full-thickness cutaneous wound model in mice, followed by a systematical evaluation and comparison of the effect of preserved water on wound healing efficiency in vivo. The optimal BET@COL collagen sponges were able to maintain high water content (e.g. moist microenvironment), suppress oxidative stress, improve anti-inflammation, all of which impose synergetic healing effects to promote wound closure, granulation formation, re-epithelization, cell proliferation, collagen deposition and angiogenesis. This work demonstrates a new wound dressing material as a promising candidate for wound dressing.